A prospective survey of current prostate biopsy practices among oncological urologists - (:unkn) unknown (CANADIAN J UROLOGY, 2010)
Background: Needle biopsy of the prostate is a common outpatient procedure. In March 2009, the European Association of Urology (EAU) published an updated, evidence-based Guidelines on Prostate Cancer, including recommendations for this procedure. Objective: To survey onco-urology specialists attending the 6th European Section of Oncological Urology (ESOU) meeting in Istanbul, Turkey in January 2009, to assess their biopsy practices and compare them with March 2009 EAU guidelines. Design, setting and participants: The authors designed a questionnaire and distributed it to 606 conference delegates. It was completed by 298 delegates, of whom 156 were experienced onco-urological specialists. Measurements: The survey results from the 156 experienced onco-urologist specialists were analyzed. Results and limitations: Most (59%) of the 156 respondents worked in large (> 20 bed) units, and 76% said urologists always performed the biopsies. Transrectal ultrasound (TRUS)-guided biopsy was the preferred procedure for 78% of respondents. Prostate-specific antigen (PSA) cut-off points of 4 ng/mL, 3.5 ng/mL, 3 ng/mL, and 2.5 ng/ml were used by 42%, 18%, 23%, and 8% of respondents, respectively, to determine whether a biopsy was indicated. A total of 95% of respondents gave patients prophylactic antibiotics. Another of 15% and 17% of respondents did not advise patients to stop taking warfarin or clopidogrel, respectively. A total of 23% of respondents did not give patients pre-procedure anesthesia, while others gave patients periprostatic lidocaine (31% of respondents), topical lidocaine jelly (35%), or general or spinal anesthesia (5.7%). High grade prostatic intraepithelial neoplasia (HGPIN) was considered by 71% of respondents as being a pre-malignant condition requiring a repeat biopsy. If atypical small acinar proliferation (ASAP) was reported, 62% of respondents recommended a repeat biopsy. Magnetic resonance imaging (MRI) was used to help diagnose cancer (53% of respondents), help stage cancer (83%), or help diagnose cancer recurrence (62%). Study limitations include possible difficulties with the English questionnaire. Conclusions: Many surveyed specialists were not performing prostate biopsies according to March 2009 evidence-based EAU practice guidelines, which could have adverse consequences for patients.
Keywords: prostate cancer; transrectal ultrasound; prostate biopsy; CANCER; TRIAL; PAIN; MEN